Simple Financial Statements Training for Business Actors in West Java Indonesia - Riwayati, Hedwigis Esti; Mawardi, Rizal; Sorongan, Fangky Antoneus; Amelia, Tifa Noer; Zainon, Saunah; Misman, Faridah Najuna (Dinasti Publisher, 2024)
This training aims to improve the understanding and skills of Ikanesia West Java business actors in recording financial transactions systematically and accurately. This activity is a form of community service collaboration between Perbanas Institute and Universiti Teknologi Mara Malaysia. In this training, participants are given a basic understanding of accounting, the benefits of financial record-keeping, as well as simple record-keeping techniques that can be applied in the fisheries business. With this training, it is hoped that business actors can increase transparency and efficiency in their financial management.